Identification of Antioxidant Compounds in Fig Leaves (Ficus carica L) Fractions Using LC-MS/MS (Sciences of Pharmacy, 2023)
The fig plant (Ficus carica L.) is one of the most popular ficus genera and is spread in tropical and sub-tropical regions throughout the world. Fig leaves have potential as antioxidants. The purpose of this study was to identify antioxidant compounds in the ethanol extract of fig leaves of the Iraqi variety. The research involved preparing extracts by maceration using 96% ethanol, 70% ethanol, and 50% ethanol, testing antioxidant activity and identifying their chemical structures using LC-MS/MS. Based on the results of the antioxidant activity test using the DPPH free radical scavenging method, it was shown that the 50% ethanol extract of fig leaves had a very strong antioxidant activity with an IC50 value of 23.36 µg/mL. The results of identification with LC-MS/MS, it is estimated that the compound that has the potential as an antioxidant in the fig leaves of the Iraqi variety is the kaempferol compound.